2018
DOI: 10.1080/17518369.2018.1492297
|View full text |Cite
|
Sign up to set email alerts
|

Temperature (latitude) and nutrient (seabird guano) effects on limno-terrestrial Tardigrada (Testechiniscus spitsbergensisandPilatobius recamieri) body size

Abstract: Surveys of terrestrial microinvertebrate morphometry, especially spatial patterns of body size at wider geographical scales, including the polar regions, are very scarce. In this study, we focused on Tardigrada, common limno-terrestrial microinvertebrates. Considering Bergmann's rule, originally formulated for endothermic animals, we tested the hypothesis that body length of limno-terrestrial tardigrades augments with increasing latitude and decreasing temperature. Since some of our sampling areas adjoined sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 63 publications
1
4
0
Order By: Relevance
“…But, of course, the impact of temperature is strongly species-dependent, which has been confirmed by other authors (e.g. Sømme & Meier 1995;Ramlov & Westh 2001;Li & Wang 2005a, 2005bHengherr et al 2009;Zawierucha et al 2018;Neves et al 2020). Nevertheless, as shown in Table I, some tardigrade species have been cultured with success at different temperatures.…”
supporting
confidence: 65%
“…But, of course, the impact of temperature is strongly species-dependent, which has been confirmed by other authors (e.g. Sømme & Meier 1995;Ramlov & Westh 2001;Li & Wang 2005a, 2005bHengherr et al 2009;Zawierucha et al 2018;Neves et al 2020). Nevertheless, as shown in Table I, some tardigrade species have been cultured with success at different temperatures.…”
supporting
confidence: 65%
“…However, there has been considerable sampling effort along the west coast, particularly around Isfjord (Longyearbyen and Barentsburg) and Kongsfjord (Ny-Ålesund). From these studies, projects and campaigns a large number of articles have arisen (Coulson et al 2014a;Gillespie et al 2016;Luoto et al 2016;Kolicka 2017;Zawierucha et al 2018). It is curious then that with limited sampling undertaken during this project that such a large percent of the species identified were new records if these species do indeed occur in habitats in the west of the archipelago.…”
Section: The Invertebrate Fauna Of Edgeøyamentioning
confidence: 99%
“…Based on data assessing springtails, mites and tardigrades from sites affected by marine vertebrates and nonimpacted control sites (Zawierucha et al 2015b(Zawierucha et al , 2016(Zawierucha et al , 2017(Zawierucha et al , 2018Zmudczyńska-Skarbek et al 2015, 2017Bokhorst and Convey 2016;Bokhorst et al 2019a, b), we found significant vertebrate influence on terrestrial invertebrate community composition regardless of their taxonomic affiliation or geographic location (Model 1, factor: Vertebrates; F = 111.65, df = 1, p < 0.001; Suppl. Table 1, Fig.…”
Section: Meta-analysis Of Numerical Datamentioning
confidence: 86%
“…Datasets available from the Arctic included the taxonomic composition of springtail communities (35 species) from Hamburgbukta (NW Spitsbergen), Isfjorden (central Spitsbergen) and Bjørnøya (Zmudczyńska-Skarbek et al 2015, 2017, mites (Oribatida, Mesostigmata, in total 48 species) from Hamburgbukta and Isfjorden (Zmudczyńska-Skarbek et al, unpublished data), and Bjørnøya (Zmudczyńska-Skarbek et al 2017), and tardigrades (43 species) from Svalbard (Hornsund, Kongsfjorden, Nissenfjella, Nordaustlandet, Amsterdamøya, Danskøya, Fuglesongen, Phippsøya, Parrøya, and Prince Karl Forland, Zawierucha et al 2015bZawierucha et al , 2016Zawierucha et al , 2017Zawierucha et al , 2018. The Antarctic datasets contained records of springtails (6 species) and mites (Oribatida, Mesostigmata, Prostigmata, in total 9 species) from Signy Island (South Orkney Islands), Byers Peninsula (Livingston Island, South Shetland Islands), and islands within Ryder Bay (south-east Adelaide Island) (Bokhorst and Convey 2016;Bokhorst et al 2019a, b).…”
Section: Meta-analysis Of Numerical Datamentioning
confidence: 99%
See 1 more Smart Citation